Efek Kombinasi Ekstrak Metanol Daun Sirih (Piper Betle Linn.) dengan Antibiotik Amoxicillin, Chloramphenicol dan Cotrimixazole Terhadap Daya Hambat Pertumbuhan Bakteri S.aureus dan E.coli - Reza Muchlas Fauziansyah (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2018)
Introduction: Staphylococcus aureus and Escherichia coli are the most causes of infectious diseases. Handling of infections has been using antibiotics that can cause resistance and disbiosis of intestinal microbiota. The use of adjuvants from herbs is needed to increase the effectiveness of antibacterials and prevent dibiosis, one of which uses betel leaves. Research on the combination of betel leaves with amoxicillin (AMX), cotrimoxazole (CTX), and chloramphenicol (CHL) needs to be done.Method: Combined Zone of Inhibition (ZOI) Test using Ameri-Ziaei Double Antibiotic Synergism Test (AZDAST) in Nutrient Agar. A single or a combination of the Minimum Inhibitivity Concentration (MIC) is carried out by macrodilution. The Minimum Bactericidal Concentration (MBC) is determined by the presence of a clear area formed on the petri dish. The nature of the interaction between MIC and MBC betel leaves and antibiotics was calculated using the Checkerboard assay.Result: Betel leaf extract has a zone of inhibition on S. aureus greater than E. coli (32.66 ± 6.42 mm / 23.33 ± 4.16 mm). The MIC of betel leaf, AMX, CTX, and CHL against S.aureus were 0,0039mg/ml, 0,0078mg/ml, 0,0078mg/ml, and 0,0078mg/ml as well as against E.coli were 0,03125mg/ml, 0,0078mg/ml, 0,0078mg/ml and 0,0009mg/ml. The MBC of betel leaf, AMX, CTX, and CHL against S.aureus were 0,0039mg/ml, 0,0078mg/ml, 0,0078mg/ml, 0,0078mg/ml and also against E.coli were 0,03125mg/ml, 0,0078mg/ml, 0,0078mg/ml, and 0,00097mg/ml. The combination of betel leaves with antibiotics increase the MIC and MBC against S.aureus and E.coliConclusion: The combination of betel leaves is antagonistic with AMX, CTX, and CHL against S. aureus. The combination of betel leaves is additive with CHL and is antagonistic with AMX and CTX against E. coli